2002
DOI: 10.1016/s0893-133x(02)00340-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gi Proteins in the Antidepressant-like Effect of Amitriptyline and Clomipramine

Abstract: The effect of the i.c.v. administration of pertussis toxin (PTX) and antisense oligodeoxynucleotides directed against the ␣ subunit of different Gi-proteins (anti-For the past several decades, antidepressant drugs have been widely used in the treatment of clinical depression and other psychiatric disorders. Several distinct pharmacological compounds show therapeutic efficacy. These include monoamine oxidase inhibitors, tricyclic compounds, selective serotonin and norepinephrine reuptake inhibitors, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…It remains unclear as to how amitriptyline-evoked G i/o activation is related to the antidepressive effect of amitriptyline. An in vivo study showed that intracerebroventricular administration of PTX completely prevented the antidepressant-like effect of amitriptyline in the mouse forced swimming test (64). Furthermore, Galeotti et al (64) showed that G i1 , Gi2, G i3 , and G o1 , but not G o2 , play important roles in the antidepressant-like effect of amitriptyline, administering antisense oligonucleotides against the ␣-subunits of the G protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear as to how amitriptyline-evoked G i/o activation is related to the antidepressive effect of amitriptyline. An in vivo study showed that intracerebroventricular administration of PTX completely prevented the antidepressant-like effect of amitriptyline in the mouse forced swimming test (64). Furthermore, Galeotti et al (64) showed that G i1 , Gi2, G i3 , and G o1 , but not G o2 , play important roles in the antidepressant-like effect of amitriptyline, administering antisense oligonucleotides against the ␣-subunits of the G protein.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study showed that intracerebroventricular administration of PTX completely prevented the antidepressant-like effect of amitriptyline in the mouse forced swimming test (64). Furthermore, Galeotti et al (64) showed that G i1 , Gi2, G i3 , and G o1 , but not G o2 , play important roles in the antidepressant-like effect of amitriptyline, administering antisense oligonucleotides against the ␣-subunits of the G protein. This study confirms the importance of PTX-sensitive G i/o in the effect of antidepressants such as amitriptyline and further elaborates a novel mechanism that could explain the efficacy of antidepressants, increased GDNF production by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the above ODNs and their characterization are described in a previous paper (Galeotti et al, 2002) and base composition is reported in Table 1. As previously established (Standifer et al, 1996;Sanchez-Blazquez and Garzon, 1998;Galeotti et al, 2002), we used the lowest effective aODN doses (25 μg) to ensure the selectivity of the response in hot plate test. The aODNs, mODNs and dODNs were supplied to mice by i.c.v.…”
Section: Antisense Oligodeoxynucleotidesmentioning
confidence: 99%
“…Previous in vivo studies have demonstrated behavioral response to antidepressants involves increasing GDNF production and PTX-sensitive signaling in the brain. 39,40) The potentiating Gi/o protein signaling efficacy of antidepressant by combination treatment with Gi/o protein activator could boost endogenous GDNF and BDNF production. This would suggest a potential mechanism that could be targeted in the development of novel antidepressant treatments.…”
Section: +mentioning
confidence: 99%